Bioethical study on the utilization of empty fruit bunch waste in the palm oil industry (elaeis guineensis) from an environmental, social and economic perspective - Affrina Firdayani; Frisky Septiani Simanjuntak; Putri Lestari Simbolon; Mhd Yusuf Nasution; Nurbaity Situmorang (EduMatika: Jurnal MIPA, 2026)
Oil palm empty fruit bunches (OPEFB) are one of the main solid biomass residues in the palm oil industry, accounting for approximately 20–25% of the total processed raw materials. Management of this waste is a strategic issue in supporting industrial sustainability, particularly from an environmental, social, and economic perspective. This study aims to analyze the bioethical dilemma in the utilization of OPEFB through a descriptive qualitative approach using field observation and literature review methods. The analysis was conducted by grouping findings based on environmental, social, and economic perspectives, and interpreted using bioethical principles such as responsibility, justice, and sustainability. The results indicate that OPEFB has significant potential as a value-added resource, such as organic fertilizer, bioenergy, biomaterials, and lignocellulose-based industrial products. This utilization provides benefits in waste reduction, community empowerment, and increased economic value. However, the bioethical dilemma arises from the imbalance between the industry's economic interests and environmental protection and community welfare. Therefore, sustainable OPEFB management is needed through the integration of environmental, social, and economic aspects based on bioethical principles to achieve ethical and sustainable industrial development.